The Relationship between Physical Environment and Venue Facilities for Aerobic on Aerobic Dance Exercise Behavior - Apiwan; Intahlor, Pimprapa (Academic Journal of Thailand National Sports University, 2022)
This research aimed to investigate the relationship between physical environment and venue facilities for aerobic dance and aerobic dance exercise behavior. The sample of this study selected by cluster random sampling included 450 people who take aerobic exercises in Sukhothai Province and Phitsanulok Province. The obtained data were analyzed by means of percentages, means, standard deviation, chi - square tests, Peason product - moment correlation coefficient, exploratory factor analysis and multiple regression The results of this research were as followed: The majority of the sample commuted to take aerobic exercises alone by bicycles/ motorcycles. They came to the aerobic place before the dance started and got 10-15 minutes rest after the dance. They got aerobic exercises 4 times a week The aerobic exercise behavior was not correlated with frequency of aerobic exercise at a .05 level of significance. The physical environment and venue facilit'es for aerobic dance were correlated with frequency of aerobics exercise with no significart difference at .05 level. Physical environment and venue facility factors affected the frequency of aerobic exercises. It was found that three the best predicted variables that affected aerobic exercise behavior at the .05 level of statistic significance were: 1) the beautiful shady environment that included variables of tree trimming and shaping, landscape gardening and setting the place in harmony with nature, 2) the location suitable for aerobic exercises that included variables of area size, area layout and solid waste management, and 3) The ventilation of the area that included variables of the fresh air as well as circulation of air. The recommendation from the research is that local agencies such as provincial administration organization or subdistrict administration organization in Sukhothai Province and Phitsanulok Province that involve in encouraging their people to take exercises for their good health should adapt the results of this research in providing the exercise venue with better physical environment and facilities in order to encourage people to take more exercises.